Pengaruh Lingkungan Kerja dan Promosi Jabatan terhadap Disiplin Kerja melalui Kepuasan Kerja sebagai Variabel Intervening (Survei Pada PT LEN Industri (Persero) Kota Bandung) - Neng Syifa Sari Fatimah; Ridlwan Muttaqin; Palupi Permata Rahmi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to examine the impact of working conditions and promotions on employee discipline, with job satisfaction as an intervening factor, at PT LEN Industri (Persero) in Bandung. The research approach is quantitative, using descriptive and verificative methods. Information was collected from primary sources through a questionnaire survey distributed to 80 participants, along with additional data from secondary sources. The data were then analyzed using descriptive and verificative analysis, as well as path analysis with the assistance of SPSS version 26 software. Research findings reveal that working conditions have a significant impact on job satisfaction, whereas promotions do not show a significant effect on job satisfaction. Additionally, working conditions and job satisfaction together significantly influence employee discipline, but promotions alone do not affect discipline. Finally, working conditions and promotions through job satisfaction are found to have a significant effect on employee discipline.